Chemistry and biochemistry of dietary carotenoids: bioaccessibility, bioavailability and bioactivities - Cheng Yang; Lianfu Zhang; Rong Tsao (Journal of Food Bioactives, 2020)
Carotenoids are one of the major food bioactives that provide humans with essential vitamins and other critically important nutrients that contribute to the maintenance of human health. This review provides a summary of the most current literature data and information on most recent advances in dietary carotenoids and human health research. Specifically, it addresses the occurrence and distribution of carotenoids in different dietary sources, the effect of food processing and impact of gastrointestinal digestion on the bioaccessibility, bioavailability and bioactivities of dietary carotenoids. Emphasis is placed on the antioxidant and anti-inflammatory effects of carotenoids and their optical/geometric isomers and ester forms, and the molecular mechanisms behind these actions. A particular focus is also on the modulatory ability of carotenoids on biomarkers related to low-grade inflammation, immune response and gut health.